2020
DOI: 10.1097/md.0000000000022049
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum albumin-to-creatinine ratio in patients with acute myocardial infarction

Abstract: The long-term association between serum albumin-to-creatinine ratio (sACR) and poor patient outcomes in acute myocardial infarction (AMI) remains unclear. This study aimed to determine whether sACR was a predictor of poor long-term survival in patients with AMI. This was a study of patients with AMI in the emergency department (ED) from the retrospective multicenter study for early evaluation of acute chest pain (REACP) study. The patients were categorized into tertiles (T1, T2, and T3) based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…They found that patients with lower sACR had higher all-cause mortality and adverse events during a median follow-up of 10.7 months compared with patients with higher sACR. 28 They concluded that sACR improved the prognostic value of the GRACE score.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that patients with lower sACR had higher all-cause mortality and adverse events during a median follow-up of 10.7 months compared with patients with higher sACR. 28 They concluded that sACR improved the prognostic value of the GRACE score.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lower levels of SA were also associated with cardiac and overall mortality. 28 A recent study (2250 patients with AMI) investigated sACR for the prediction of poor long-term survival in patients with AMI. 28 Other risk scores were also concomitantly evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The urine albumin-to-creatinine ratio (uACR) has been verified to be independently associated with increased long-term risks of cardiovascular and total mortality in survivors of MI ( 28 ). The serum albumin-to-creatinine ratio (sACR) was found to be an independent prognostic biomarker in patients with AMI on admission to the emergency department and a useful biomarker for early risk stratification of patients with AMI ( 82 ).…”
Section: Biomarkersmentioning
confidence: 99%